Comparison of safranin-O cationic dye removal using different parts of Angelica sylvestris L. biomass: Non-linear isotherms, kinetics, thermodynamics, and error analysis - Habipoglu, Melek Kubra; Isik, Birol; Cakar, Fatih (ELSEVIER SCI LTD, 2026)
Angelica sylvestris L. roots, stems, and flowers were utilized to extract safranine O (SO) dye from wastewater. Adsorbent characterization was carried out using FTIR-ATR, SEM, BET, and pHpzc studies. Models of Langmuir, Freundlich, Temkin, Dubinin-Radushkevich (D-R), Jovanovic non-linear isotherms were fitted to adsorption raw data. A good match between the equilibrium values and the Langmuir isotherm was observed. For Angelica sylvestris L. roots, stems, and flowers, the Langmuir isotherm model at 298 K temperature yielded the maximum adsorption capacity of 86.00 mg/g, 53.45 mg/g, and 50.42 mg/g, respectively. The pseudo-second order kinetic model was followed by the kinetic results, though. For the reproducibility of the results and the applicability of kinetic and adsorption isotherms, error functions were computed. Entropy, Gibbs free energy, and enthalpy thermodynamic constants were computed under equilibrium. According to the results, SO dye adsorption is an exothermic, spontaneous process. Investigations were also conducted into how the concentration of monovalent NaCl and divalent CaCl2 affected the adsorption process. Calculations have shown that the roots, stems, and flowers of A. sylvestris L. can be effectively used as a potential low-cost and reusable material substitute for the removal of cationic dyes from wastewater treatment.
Keywords: Adsorption; A. sylvestris L. biomass; Safranine O; Isotherms; Kinetics; Thermodynamics; METHYLENE-BLUE DYE; AQUEOUS-SOLUTIONS; T DYE; ADSORBENT; WASTE; EQUILIBRIUM; EFFICIENCY; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Engineering